2016
DOI: 10.1080/15548627.2016.1230583
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone suppresses hepatocarcinogenesis via DAPK2 and SQSTM1-dependent selective autophagy

Abstract: Recent studies have demonstrated a critical association between disruption of cellular thyroid hormone (TH) signaling and the incidence of hepatocellular carcinoma (HCC), but the underlying mechanisms remain largely elusive. Here, we showed that disruption of TH production results in a marked increase in progression of diethylnitrosamine (DEN)-induced HCC in a murine model, and conversely, TH administration suppresses the carcinogenic process via activation of autophagy. Inhibition of autophagy via treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 36 publications
1
52
0
Order By: Relevance
“…We previously showed that several protein-coding genes, including those encoding endoglin [39], pituitary tumor-transforming 1 (PTTG1) [27], Dickkopf 4 (DKK4) [40], ubiquitin-like with PHD and ring finger domains 1 (UHRF1) [37], and death-associated protein kinase 2 (DAPK2) [1], as well as non-coding genes, such as microRNA-214 (miR-214) [41] and BC200 [42], are regulated by T 3 /TR in HepG2-TR cell lines. The finding that TUG1 is downregulated by T 3 /TR, together with previously demonstrated oncogenic activity of TUG1 in HCC suggests that T 3 /TR suppresses cell growth by regulating protein-encoding genes and non-coding RNAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed that several protein-coding genes, including those encoding endoglin [39], pituitary tumor-transforming 1 (PTTG1) [27], Dickkopf 4 (DKK4) [40], ubiquitin-like with PHD and ring finger domains 1 (UHRF1) [37], and death-associated protein kinase 2 (DAPK2) [1], as well as non-coding genes, such as microRNA-214 (miR-214) [41] and BC200 [42], are regulated by T 3 /TR in HepG2-TR cell lines. The finding that TUG1 is downregulated by T 3 /TR, together with previously demonstrated oncogenic activity of TUG1 in HCC suggests that T 3 /TR suppresses cell growth by regulating protein-encoding genes and non-coding RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormone (3,3 ,5-triiodo-l-thyronine; T 3 ) regulates cell homeostasis, growth, development, autophagy and metabolism [1] through binding to thyroid hormone receptors (TR) [2]. Human TRs are encoded by TRα1 and TRβ1 genes located on chromosomes 17 and 3, respectively [3].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, DAPK family members not only participate in classic cell death pathways but also contribute to autophagy induction [49]. Of relevance for this study is that overexpression of DAPK2 induces autophagy in 293T HEK cells and in hepatocellular carcinoma [29,31]. Furthermore, p73 regulates ATG5 and DRAM-1 expression, key regulators of autophagy [21,22].…”
Section: Dapk2 Depletion Attenuates Atra-but Not Ato-induced Autophagymentioning
confidence: 94%
“…DAPK2 is a member of the serine-threonine kinase DAPK family, including its closest homolog, DAPK1. To date, several reports describe a role for DAPK2 in TRAIL-, TNF-a/FAS receptor-, E2F1-, or epigallocatechin-3-gallate-mediated cell death [24][25][26][27][28], as well as in autophagy, by increasing LC3 dot formation and regulating mammalian target of rapamycin phosphorylation [29][30][31]. Within the human hematopoietic system, DAPK2 is predominantly expressed in neutrophil and eosinophil cells, whereas DAPK1 and -3 are mainly expressed in monocytes [32].…”
Section: Introductionmentioning
confidence: 99%
“…Only a few interactors of DAPK2 have been identified so far [32][33][34]. Accordingly, just a limited number of DAPK2 substrates is currently known: myosin II regulatory light chain, the mTOR binding partner raptor [35], the autophagy receptor protein p62/SQSTM [36] and the core autophagic machinery protein Beclin-1 [37]. DAPK2 function is tightly controlled at multiple layers, suggesting a relevant function for this protein that needs to be under strict and fine regulation.…”
Section: Discussionmentioning
confidence: 99%